The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1039/c3nr04743a
|View full text |Cite
|
Sign up to set email alerts
|

Defect-related ferromagnetism in ultrathin metal-free g-C3N4 nanosheets

Abstract: Ultrathin metal-free g-C3N4 nanosheets with intrinsic room temperature ferromagnetism were synthesized by heating urea in an airtight container at different temperatures. Results indicate that the samples' saturation magnetization increases with the carbon defect concentration, revealing its carbon defect related ferromagnetism. Moreover, we further confirmed the defect induced ferromagnetic nature by ab initio calculations. It is believed that this finding highlights a new promising material toward realistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
83
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(91 citation statements)
references
References 39 publications
4
83
0
Order By: Relevance
“…S2) show that the SSA and pore volume of the NMGCN powder are about 220 m 2 , confirming the presence of more photocatalytic active sites in the NMGCNs. This is further confirmed by the ferromagnetic measurements because theoretical and experimental studies suggest that the ultrathin GCNNs show intrinsic ferromagnetism at room temperature due to the presence of hydrogen dangling bonds [28,48]. As expected, the M-H curves of NMGCNs and GCNNs show an obvious hysteresis loop with saturation magnetization (Fig.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…S2) show that the SSA and pore volume of the NMGCN powder are about 220 m 2 , confirming the presence of more photocatalytic active sites in the NMGCNs. This is further confirmed by the ferromagnetic measurements because theoretical and experimental studies suggest that the ultrathin GCNNs show intrinsic ferromagnetism at room temperature due to the presence of hydrogen dangling bonds [28,48]. As expected, the M-H curves of NMGCNs and GCNNs show an obvious hysteresis loop with saturation magnetization (Fig.…”
Section: Resultssupporting
confidence: 68%
“…S11). However, the saturation magnetization (Ms) value of the NMGCNs reaches 0.04 emu g −1 , which is about five times larger than that for the GCNNs (0.008 emu g −1 ) and also much higher than previously reported values for the ultrathin GCNNs [28,48]. Notably, this is the highest Ms value among the previous reports for GCN.…”
Section: Resultsmentioning
confidence: 57%
“…It has been previously reported that carbon vacancies can induce the ferromagnetism in GCN at room temperature owing to spin-polarized conduction electrons in the spin-down branch. [ 25 ] Thus, this assumption can be confi rmed by the magnetic measurements. An obvious hysteresis hoop is observed in the curve of the magnetic fi eld dependence of the magnetization ( M-H ) recorded at 300 K ( Figure S4, Supporting Information), confi rming the room-temperature ferromagnetism of HGCN.…”
Section: Resultsmentioning
confidence: 94%
“…Five peaks obtained from the deconvolution of the C-1s peak are centered at 284.7 eV (C=C), 285.3 eV (C-C, C-H), 286.4 eV (C-OH), 287.3 eV (C-O-C) and 288.3 eV (C=O). 22 The numerous functional groups enable K-GQDs to have good solubility in water. The intensity of the peaks at 284.7 eV and 285.3 eV are stronger, meaning that C=C, C-C and C-H are the major chemical configuration in K-GQDs, in particular, C=C is related to sp 2 hybridization while C-C and C-H are related to the sp the K-2p 3/2 orbitals are present at 294.2 eV and 294.5 eV.…”
Section: Resultsmentioning
confidence: 99%